The effects on colour, texture and sensory attributes achieved by washing black tilapia flesh with a banana leaf ash solution - Mohsin, Md.; Bakar, Jamilah; Selamat, Jinap (Blackwell Science, 1999)
The washing of freshwater fish with clarified solutions of banana leaf ash to remove the muddy odour and flavour is common both in Bangladesh and Indian households. However, no scientific study has been done to evaluate its effectiveness. This study was, therefore, done to show the effect of the washing treatments on the following sensory attributes: odour; flavour; colour and texture. The latter two attributes were also measured by instrumental methods. The experimental animal was black tilapia (Oreochromis mossambicus), which was filleted and each fillet washed by a clarified solution of banana ash (either originally 5 or 7% ash). Controls were fillets washed in ice-slush only. Those fillets washed in 5% ash for 5 min were the most acceptable for eating, cooked or uncooked. There were highly significant differences (p < 0.01) in the L-colour values (lightness values) when treated fillets were compared to untreated fillets. However cook-ing the fillets reduced the difference, making it not significant. Texture was significantly affected by washing and this was retained in cooked fillets, however this was particularly significant using a 7% solution which gave a softer fillet.